Molecular Identification of Enterocytozoon bieneusi Isolates from Nigerian Children - Adekunle Bamidele Ayinmode; Oladele Teslim Ojuromi; Lihua Xiao (Journal of Parasitology Research)
A study was conducted to detect and identify enteric microsporidian species in 43 children from Oyo state, Nigeria. Using nested polymerase chain reaction, 9.3% of the children were identified as positive for Enterocytozoon bieneusi. DNA sequencing of the PCR products showed the presence of three known genotypes (two isolates of genotype D and one of genotype K) and one new genotype. This study suggests that either human or animal (or both) could be the infection source for the children, since identified genotypes D and K have been previously detected in both immunocompromised and immunocompetent patients and domestic animals. The identification of high diversity also suggests intensive transmission of microsporidiosis in the studied area.